A Participatory Approach for Envisioning a Smart City. (December 2016) - van Waart, Peter; Mulder, Ingrid; de Bont, Cees
The work we will be discussing here explores how government, industry, the university, and the citizens of a city can arrive through a participatory design approach at an increased and mutual understanding and a shared vision of a desired smart city of the future. Elaborating upon insights from transition management studies and from the quadruple-helix knowledge production model, our work proposes a participatory approach for prototyping future cities that embraces practice-oriented design research activities and thus aims for practical impact. We will report on two cases, GovJam and Hackday Data of the Crowds, in which stakeholders were able to acquire through participatory prototyping an understanding of the possibilities of technology in city services of the future. Results from these sessions show that participating stakeholders indeed gained a new perspective upon issues facing the city, due to an increased awareness and understanding of, and empathy for, the interests of other stakeholders. We also found indications that transfer of knowledge was taking place from the prototyping sessions to the daily practice of participants working in the public sector.